The genetic source tracking of human urinary exosomes - Zhu, Qingfu; Cheng, Liming; Deng, Chunyu; Huang, Liu; Li, Jiaoyuan; Wang, Yong; Li, Meng; Yang, Qinsi; Dong, Xianjun; Su, Jianzhong; Lee, Luke P.; Liu, Fei (Proceedings of the National Academy of Sciences - PNAS, 2021)
The genetic origins of nanoscale extracellular vesicles in our body fluids remains unclear. Here, we perform a tracking analysis of urinary exosomes via RNA sequencing, revealing that urine exosomes mostly express tissue-specific genes for the bladder and have close cell-genetic relationships to the endothelial cell, basal cell, monocyte, and dendritic cell. Tracking the differentially expressed genes of cancers and corresponding enrichment analysis show urine exosomes are intensively involved in immune activities, indicating that they may be harnessed as reliable biomarkers of noninvasive liquid biopsy in cancer genomic diagnostics and precision medicine.